ASUHAN KEBIDANAN ANTENATAL DENGAN LETAK SUNGSANG (Politeknik Kesehatan Kemenkes Bandung, 2022)
Pregnancy is a physiological state, but the importance of a pregnancy diagnosis cannot be ignored. Breech pregnancies are common in preterm infants and most fetuses are capable of spontaneous versioning to cephalic presentation after 34 weeks of gestation. The problem is, about 3-4% of term fetuses remain in breech presentation. Composition abnormalities in the location can complicate the birth of the fetus, if not treated properly. The purpose of this Final Project Report is to perform Antenatal Care with breech position. The method is a case report, with a midwifery management approach and using a documentation method in the form of SOAP (Subjective, Objective, Analytical, Management). Data collection techniques used interview techniques, physical examinations, documentation studies, and literature studies. The results of the assessment of subjective data from the anamnesis showed that the mother often felt fetal movement in the lower abdomen, and on Leopold's examination the lower part of the fetus was palpable round, soft and not bouncy, namely the breech presentation. Auscultation examination revealed that the punctum maximum FHR was heard on the upper left of the umbilicus. The treatment given is by doing theposition knee-chest for 3-4 times every day for 10-15 minutes and massage the acupressure points. Conclusion from the care of Mrs. U, aged 27 years, had received proper midwifery care so that the problem of breech pregnancy was resolved on the seventh day after the intervention was given. Suggestions for practice areas to provide more health education and provide information about handling breech locations.